How Cool It Is: Targeted Temperature Management for Brain Protection Post–Cardiac Arrest - Rabinstein, Alejandro A. (Seminars in Respiratory and Critical Care Medicine, 2016)
Neurological recovery often determines outcome in patients resuscitated after cardiac arrest. Temperature control as a neuroprotective strategy has become standard of care. The first randomized trials showing improved neurological outcomes in patients treated with hypothermia with a target temperature of 33°C over a decade ago led to the inclusion of this intervention in practice guidelines and the broad adoption of hypothermia protocols across the world. More recently, large randomized trials showed no difference from targeting a temperature of 33 or 36°C and no benefit from pre-hospital induction of hypothermia. Temperature control remains a crucial part of post–cardiac arrest care. However, the optimal temperature target, timing of induction, duration of temperature control, and speed of rewarming are unclear. Similarly, the value of targeted temperature management in cases of in-hospital arrest and non-shockable rhythms is unknown. This article reviews the neuroprotective mechanisms of hypothermia, the evidence supporting targeted temperature management after cardiac resuscitation, areas of persistent uncertainty and controversy, and future research directions.
Keywords: cardiac arrest; resuscitation; therapeutic hypothermia; temperature control; outcomes; neurological